The Carter Administration and the Institution of the 1977 Mandatory Arms Embargo against South Africa: Rhetoric or Active Action? (Historia, 2021)
EnglishWhen Jimmy Carter took office as President of the United States in January 1977, he faced a difficult task: human rights activists worldwide expected him to take serious action against the South African Government because of its policy of apartheid (which they viewed as a gross violation of human rights), as well as the military build-up of the South African government and the question of independence for South West Africa (Namibia), where South Africa’s administration and military presence was regarded as illegal. During the presidential campaign of 1976, Carter had declared himself a fierce supporter of human rights and vowed that he would do anything in his power to act against violators of human rights. Now that he had been elected, he had to act on his promises. The question is, did he seriously mean to take action against the South African government, or was it again merely the same verbal rhetoric that previous US governments had made themselves guilty of? This article investigates statements and actions by the Carter administration vis-à-vis South Africa during its first ten months in office, as well as the factors that played a role in determining the decision to impose a mandatory arms embargo against South Africa. In conclusion, it has been found that although Carter and his administration continuously verbally castigated the South African government, in the end it was merely a case of anti-apartheid rhetoric. The fact is that the mandatory embargo did not really constitute anything new as far as US policy towards South Africa was concerned.    AfrikaansDie Carter-Administrasie en die Instelling van die 1977-Verpligte Wapenverbod teen Suid-Afrika: Retoriek of Aktiewe Optrede? Met Jimmy Carter se aanvaarding van die presidentskap van die Verenigde State van Amerika in Januarie 1977, het hy voor ŉ moeilike taak te staan gekom. Menseregte-aktiviste vanoor die wêreld het van hom verwag om strenger teen die Suid-Afrikaanse regering op te tree weens laasgenoemde se apartheidsbeleid (wat as ŉ verregaande skending van menseregte beskou is), asook weens die Suid-Afrikaanse regering se opgaring van militêre voorrade en Suidwes-Afrika (Namibië) se onafhanklikheids-vraagstuk. Suid-Afrika se administratiewe en militêre teenwoordigheid in laasgenoemde is naamlik as onwettig beskou. Gedurende die presidensiële verkiesingsveldtog van 1976, het Carter verklaar dat hy ŉ vurige voorstander van menseregte is en onderneem dat hy alles in sy vermoë sou doen om teen diegene op te tree wat hulle aan die skending van menseregte skuldig maak. Na sy verkiesing, was dit nou tyd om hierdie beloftes na te kom. Die vraag is of hy werklik ernstig was daaroor om teen die Suid-Afrikaanse regering op te tree, en of hierdie uitsprake van hom nie maar net weer dieselfde verbale retoriek was wat ook deur vorige Amerikaanse regerings gebruik is nie. Hierdie artikel ondersoek die verklarings en optrede van die Carter-administrasie teenoor Suid-Afrika gedurende Carter se eerste tien maande aan bewind, asook die faktore wat ŉ rol gespeel het in die neem van die besluit om ŉ verpligte wapenverbod teen Suid-Afrika in te stel. Ten slotte word bevind dat, hoewel Carter en sy administrasie die Suid-Afrikaanse regering voortdurend mondelings terreggewys het, dit maar net weer ŉ voorbeeld van anti-apartheid retoriek was. Die feit is dat die verpligte wapenverbod nie werklik as ŉ nuwe verwikkeling in die Amerikaanse beleid teenoor Suid-Afrika beskou kan word nie.
Keywords: Arms embargo implementation; arms embargo; arms industry; arms shipments; Carter administration; nuclear weapons; sanctions; South African Apartheid Government; United States foreign policy; US anti-apartheid movement; Amerikaanse anti-apartheidsbeweging; Amerikaanse buitelandse beleid; Carter-administrasie; kernwapens; sanksies; Suid-Afrikaanse apartheidsregering; wapenbesendings; wapenindustrie; wapenverbod toepassing; wapenverbod